Detecção de Intrusões baseada em Séries Temporais - Dalmazo, Bruno Lopes; Vogt, Francisco; Perlin, Tiago; Nunes, Raul Ceretta (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2008: Companion Proceedings of the 8th Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2008.20903, 2008)
This article does not have an abstract.